Enzymatic properties of carboxymethylcellulase and beta-glucosidase from Aspergillus nidulans - Maeng, P. J . (Serdang, Selangor (Malaysia), 2013)
Crude enzyme solution prepared from the culture filtrate of CMC minimal liquid medium was fractionated through a three-step purification procedure: chromatography on Bio-Gel P-150, DEAE-Sephadex A-50 and Sephadex G-100 or G-200. Three CmCase components (F-I-Ia, F-I-Ib and F-II-Ia) and three Beta-glucosidase components (P-I-Ia, F-I-Ib and F-II-Ia) were prepared. All the CmCase components showed their highest activities at pH 5.0, while the pH-optima of the Beta-glucosidase components were all 6.0. Temperature-optima were 55 deg C for P-I-Ia and P-II-Ia, 60 deg C for P-II-Ib, 45 deg C for F-I-Ia, 40 deg C for F-I-Ib and 50 deg C for F-II-Ia. Beta-glucosidase components showed specificities toward cellooligosaccharides and sugar derivatives with Beta-glucosidic linkage such as cellobiose, cellotriose, cellotetraose, cellopentaose, PNPG, sophorose and salicin. All the three components not only hydrolyzed substrates to produce glucose but also transferred it to other molecules. P-I-Ia showed a different mode of action from the other two components in that it did not accumulate transglucosylated products in detectable amounts when reacted with cellooligosaccharides